The Values Supporting the Creativity of Employees - Balková, Miluše; Lejsková, Pavla; Ližbetinová, Lenka (Frontiers in Psychology, 2022)
In Industry 4.0 completely new production worlds are emerging, where robots are becoming a key element and where common human skill activities and thinking are commonly surpassed. The growing degree of automation and the interconnection of the digital and the real-world create an environment that requires a set of interdisciplinary skills. For the sustainability of enterprises in this environment, human creativity acquires an irreplaceable role. The aim is to compare the application of selected values in corporate culture, which creates a space for increasing the creativity of employees from the perspective of different sizes of enterprises. The research sample consists of 1,716 companies of the Czech and Slovakia that participated in the questionnaire survey. The results of the independent T-test confirmed significant differences in the applied values between the countries being compared. Differences in terms of business size have been further explored through the ANOVA test and the Tukey HSD test. The results subsequently confirmed that the values: work meaningfulness, passion for work, and trust are applied more significantly to microenterprises in both the countries, creating an environment that supports creativity.